THE INFLUENCE OF GROSS REGIONAL DOMESTIC PRODUCT ON POVERTY IN INDONESIA - Irma Hardianty; Abdul Aziz Ahmad; Lilis Siti Badriah (PARAMETER, 2023)
The main goal of economic development is no longer focused on aspects of high economic growth but on overcoming poverty with a continuously developing economy. This study aims to analyze the Gross Regional Domestic Product of the primary, secondary, and tertiary sectors on poverty in Indonesia from 2010 - 2020. The research method used is panel data multiple linear regression analysis. The results showed that the primary industry and the secondary sector had a significant adverse effect on poverty in Indonesia. In contrast, the tertiary sector had no impact on the poverty rate in Indonesia. This research implies that the central and regional governments need to increase capital allocation in the primary sector by improving supporting infrastructure that can increase people's income to reduce poverty. In carrying out development in the secondary sector, the government needs to open new economic areas oriented towards labor-intensive industries to reduce poverty. In overcoming the problem of poverty, it is necessary to have the government's role in improving the quality of human resources, such as improving education and health facilities, as well as a technological renewal that all levels of society can feel. ABSTRAK Tujuan utama dari pembangunan ekonomi tidak lagi menitikberatkan pada aspek pertumbuhan ekonomi yang tinggi, melainkan bagaimana mengatasi angka kemiskinan dengan perekonomian yang terus berkembang. Penelitian ini bertujuan untuk menganalisis Produk Domestik Regional Bruto sektor primer, sektor sekunder dan sektor tersier terhadap kemiskinan di Indonesia pada tahun 2010 - 2020. Metode penelitian yang digunakan adalah analisis regresi linear berganda data panel. Hasil penelitian menunjukkan sektor primer dan sektor sekunder berpengaruh negatif signifikan terhadap kemiskinan di Indonesia, sementara sektor tersier tidak berpengaruh terhadap tingkat kemiskinan di Indonesia. Implikasi dari penelitian ini pemerintah pusat maupun daerah perlu meningkatkan alokasi modal di sektor primer melalui perbaikan sarana prasarana penunjang yang dapat meningkatkan pendapatan masyarakat sehingga mampu mengurangi kemiskinan. Dalam melaksanakan pembangunan di sektor sekunder pemerintah perlu membuka daerah ekonomi baru yang berorientasi pada industri padat karya, sehingga mampu mengurangi kemiskinan. Dalam mengatasi masalah kemiskinan perlu adanya peran pemerintah dalam meningkatkan kualitas sumberdaya manusia seperti peningkatan fasilitas pendidikan dan fasilitas kesehatan serta pembaharuan teknologi yang dapat dirasakan semua kalangan masyarakat.